La planificación estratégica y los estándares en la gestión escolar de la Unidad Educativa Jatari Unancha en la parroquia Zumbahua cantón Pujilí provincia de Cotopaxi - Caisaguano Vega, Luis Segundo (2015)
This research trains, through workshops and educational guidance, the teachers and the students' update of “Jatari Unancha” Educative unit, “Guayama” based, on strategic planning to improve the standards of school management. Due to the effect of strategic planning, the institution is no longer locked into a system; it is managed in a wrong way and the school management affects to development of educational quality. In this paper the “non-experimental” method is used; it is primarily based on the observation, and later analysis of the institutional environment. The strategic planning and school management standards are without doubt tools that permit the analysis, reflection, and constructive criticism of the current institutional state, and also, promote methods for developing the institutional self-assessment. Furthermore, the research methodology is based on surveys, inquiries and interviews, to inquiries and interviews, to permit the survey people results be used for training in the PEI, (the information and communications platform), as well as in the national rules and the institution Procedural Handbook for personal and professional development. Summarized, the workshop based on training into educational guidance in strategic planning and school management standards source to the organization options some options, define short and long term objectives and identify quantitative and qualitative purposes for the methodological development in the self-assessment of institution.